2006
DOI: 10.1212/01.wnl.0000204180.25361.48
|View full text |Cite
|
Sign up to set email alerts
|

Altered brain white matter integrity in healthy carriers of the APOE ε4 allele

Abstract: Although the mechanism underlying vulnerability of white matter tracts in APOE epsilon4 carriers is still unknown, these findings suggest that increased genetic risk for developing Alzheimer disease is associated with changes in microscopic white matter integrity well before the onset of dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
130
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(146 citation statements)
references
References 28 publications
15
130
1
Order By: Relevance
“…Our study showed a selective regional atrophy of transcallosal prefrontal connections in the APOE ε4 carriers. This finding is consistent with a recent diffusion tensor imaging study that showed a decline in fractional anisotropy (FA) in the entire CC (15) in healthy APOE ε4 carriers relative to noncarriers. Furthermore, measurement of transverse relaxation rates also showed a steeper slope of agerelated decline in relaxation rates in the frontal lobe and in the genu of the CC in APOE ε4 carriers, suggesting that the ε4 allele may affect frontal WM integrity by accelerating age-related changes (16).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study showed a selective regional atrophy of transcallosal prefrontal connections in the APOE ε4 carriers. This finding is consistent with a recent diffusion tensor imaging study that showed a decline in fractional anisotropy (FA) in the entire CC (15) in healthy APOE ε4 carriers relative to noncarriers. Furthermore, measurement of transverse relaxation rates also showed a steeper slope of agerelated decline in relaxation rates in the frontal lobe and in the genu of the CC in APOE ε4 carriers, suggesting that the ε4 allele may affect frontal WM integrity by accelerating age-related changes (16).…”
Section: Discussionsupporting
confidence: 92%
“…Previous neuroimaging studies of the effect of APOE on the WM have been mainly focused on its association with vascular events and/or the degree of WM ischemic lesions in the ε4 allele carriers, showing a strong correlation between the APOE ε4 allele and WM changes (12)(13)(14). Recent studies using diffusion tensor imaging (DTI) and transverse relaxation times suggested a deleterious effect of the APOE ε4 allele on the corpus callosum (CC) integrity (15,16). Although evidence in support of a global effect of APOE ε4 on the brain has been accumulating, the impact of the APOE ε4 allele on specific neural pathways is still unclear.…”
mentioning
confidence: 99%
“…This is supported by findings of a bilateral reduction in hippocampal activation during episodic retrieval in older adults (Cabeza et al, 2004;Daselaar et al, 2006). The present findings suggest that the hippocampal component of age-related episodic memory deficits might not only be due to grey matter shrinkage (Raz et al, 2005), but also reflect alterations in hippocampal WM connections (see also Persson et al, 2006).…”
Section: Discussionsupporting
confidence: 86%
“…To summarize briefly: it has been hypothesized that interhemispheric connections of the corpus callosum provide inhibition between functionally homologous areas in the left and right hemisphere (Gazzaniga, 2000). Differences in corpus callosum anatomy such as reduced volume or reduced microstructural integrity are related to lower lateralization of function in typical participants and patient groups (Hinkley et al., 2016; Just, Cherkassky, Keller, Kana, & Minshew, 2007; Persson et al., 2006). In turn, lower lateralization is associated with lower performance on cognitive tasks, including executive function tasks (Hinkley et al., 2012; Just et al., 2007; Nagel, Herting, Maxwell, Bruno, & Fair, 2013).…”
Section: Discussionmentioning
confidence: 99%